US - Japan and US - PRC trade conflict: Export growth, reciprocity, and the international trading system - Chad P. Bown; Rachel McCulloch (Asian Development Bank Institute (ADBI), 2009)
First Japan, and more recently the People's Republic of China, have pursued exportoriented growth strategies. While other Asian countries have done likewise, the cases of Japan and the People's Republic of China are of particular interest because their economies are so large and the size of the associated bilateral trade imbalances with the United States (US) so conspicuous. In this paper, we focus on the significant spillovers to the international trading system from US efforts to restore the reciprocal General Agreement on Trade and Tariffs (GATT) and the World Trade Organization (WTO) market-access bargain in the face of such large imbalances. The paper highlights similarities and differences in the two cases, including the role of explicit and implicit subsidies, foreign direct investment, technology transfer, and currency misalignment. We explore US attempts to reduce the bilateral imbalances through targeted trade policies intended to slow growth of US imports from these countries or increase growth of US exports to them. We then examine how these trade policy responses, as well as US efforts to address what were perceived as underlying causes of the imbalances, influenced the evolution of the international trading system. Finally, we compare the macroeconomic conditions associated with the bilateral trade imbalances and their implications for the conclusions of the two episodes.
Keywords: F13; 330